Highly thermally conductive liquid metal-based composites with superior thermostability for thermal management. Issue 8 (4th February 2021) - Jia, Li-Chuan; Jin, Yi-Fei; Ren, Jun-Wen; Zhao, Li-Hua; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract : Mechanically strong and thermostable composites are prepared for thermal management based on soft liquid metal and rigid aramid nanofibers. Abstract : Thermally conductive polymer composites (TCPCs) are highly desirable for thermal management in modern electrical systems and next-generation flexible electronic devices. However, the integration of superior thermal conductivity, good mechanical performance, and high thermostability in TCPCs remains a daunting challenge, due to the utilization of abundant rigid fillers (such as graphene, boron nitride and aluminum nitride) and the low thermal stability of polymer matrices. Herein, a highly thermally conductive film with excellent mechanical strength and toughness is developed based on soft liquid metal (LM) and rigid aramid nanofibers (ANFs), via a vacuum infiltration technique. The LM/ANF composite films possess superior in-plane and through-plane thermal conductivity (7.14 @ 1.68 W m −1 K −1 ) because of the formation of a tightly packed structure, in which LM droplets are randomly distributed among the well-ordered ANFs to construct efficient heat conduction networks. Meanwhile, an outstanding tensile strength of 108.5 MPa and a high toughness of 10.3 MJ m −3 are achieved in the LM/ANF composite films. Furthermore, the LM/ANF composite films also have remarkable thermostability, flexibility, and mechanical reliability, without an obvious change in the thermal conductivity even at an elevated temperature of 250 °C and after repeated folding for 1000 cycles, respectively. These admirable features shed light on the application of the LM/ANF composite films for thermal management of high-power integrated electronic devices.